Políticas Públicas y Desarrollo Rural en el Ecuador. “Propuesta centrada en la gestión de las Juntas Parroquiales. Año 2013” Estudio de caso: parroquia El Quinche, cantón Quito – provincia de Pichincha, Año 2013 - Carrillo Mediana, Geovanny Rodrigo (2015)
This research analyzes the results of various public policies for rural territorial development in the Parish The Quinche, Canton Quito, Pichincha province. Public policies and the programs: "Human Development Bond", "Ecuador without Barriers"; "Youth, Employment and Migration"; "Ecuador Healthy", "Good Living Rural", among others, have been implemented successfully in the Parish The Quinche. Parish's GAD is the leader and facilitator of programs achieving coordinate and articulate to the Canton's GAD and Provincial's GAD, the MIESS, EMAAP-Q, MIDUVI and MSP. Problems to be faced in the near future are: insufficient access basic services; disorganization of the marketing of agricultural products; insecurity and poor control of public space, the little support for cultural and artistic activities, among others. Future research should examine the effects of the strengthening of public institutions and citizen participation in the implementation of public policy and thus contribute to the debate about their effectiveness and impact on quality of life of people living in rural parishes of our country